Konflik Wilayah Laut Tiongkok Selatan dan Kejahatan Lintas Negara serta Implikasinya terhadap Ketahanan Nasional - Thontowi, Jawahir (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
This research aims to grasp to an understanding the influence of conflict of the Southern Tiongkok Sea and Transnational Organized Crime (TOC) to ASEAN peaceful and security region, as well as to the National Resilience of the Republic of Indonesia. Research method use a normative by examining relevant legal rules. Meanwhile, it is used analysis of substantive legal rules and the functioning of institutional government. The research findings are included as a follow (1) the Tiongkok government’s claim on the nine-dash lines over territory has no international legal basis. (2) The Indonesian government considers Transnational Organized Crimes, such as drug and narcotic trafficking, etc can therefore be categorized as more serious treath to the National Resilience of RI. The Indonesian government needs to take a countermeasure against Transnational Organized Crimes rather than the conflict of the Southern Tiongkok Sea. It is therefore the Indonesian government expected to take strictly control Transnational Organized Crimes over the entire territory.